A feasibility study of electrical energy generation from municipal solid waste in Iraq: Najaf case study - Othman M. Anssari; Esam A. Alkaldy; Naseem Almudhaffar; Abbas Nasir AlTaee; Nabeel Salih Ali (Institute of Advanced Engineering and Science, 2020)
In several developing countries, the electricity crisis obstructs both socio-economic and technological sustainable evolution. Also, it leads to reducing job availability due to shut down several industries or relocate to neighbouring countries to such an issue. A Najaf City is an important holy and tourist city in the middle of Iraq country. Indeed, waste management in An Najaf City needs to be reconsidered to be used as an energy source. In this article, we investigated and listed the waste quantity which produced recently (one year) respect to waste types and types of content. Data collected from the waste products for one year and are used as a key factor to study the feasibility of generating electrical energy from collected MSWs. The proposed model was simulated and tested respect to cost analysis factor of the suggested power plant by Homer pro simulation software. Results were very encouraging and competitive to the current energy production cost based on the production cost of the Kwh prospective among the conventional methods in Iraq. The proposed scenario provide proper and secure waste proposal technique with low-cost.